2017
DOI: 10.1038/s41598-017-09199-w
|View full text |Cite
|
Sign up to set email alerts
|

Exploring dengue genome to construct a multi-epitope based subunit vaccine by utilizing immunoinformatics approach to battle against dengue infection

Abstract: Dengue is considered as a major health issue which causes a number of deaths worldwide each year; tropical countries are majorly affected by dengue outbreaks. It is considered as life threatening issue because, since many decades not a single effective approach for treatment and prevention of dengue has been developed. Therefore, to find new preventive measure, we used immunoinformatics approaches to develop a multi-epitope based subunit vaccine for dengue which can generate various immune responses inside the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
227
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 304 publications
(234 citation statements)
references
References 57 publications
7
227
0
Order By: Relevance
“…Furthermore, the vaccine-TLR2 complex was found to be stable during MD simulation where protein backbone undergone some microscale-changes (⁓7.67 Å) and mild fluctuations in their side-chain residues that can occur due to the flexible regions Pandey, Bhatt, and Prajapati 2018). These results are in line with the previous study where stabilization of vaccinereceptor complex was achieved within similar time-scale (M. Ali et al 2017;Mirza et al 2016). The hydrogen bond helps in molecular recognition by providing specificity and directionality to the interaction (Hubbard and Kamran Haider 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, the vaccine-TLR2 complex was found to be stable during MD simulation where protein backbone undergone some microscale-changes (⁓7.67 Å) and mild fluctuations in their side-chain residues that can occur due to the flexible regions Pandey, Bhatt, and Prajapati 2018). These results are in line with the previous study where stabilization of vaccinereceptor complex was achieved within similar time-scale (M. Ali et al 2017;Mirza et al 2016). The hydrogen bond helps in molecular recognition by providing specificity and directionality to the interaction (Hubbard and Kamran Haider 2010).…”
Section: Discussionsupporting
confidence: 89%
“…Quality of the refined model was assigned by Ramachandran plot, ERRAT quality factor, and ProSA z-score, and the results demonstrated that the quality of the refined model was significantly improved. Since discontinuous B-cell epitopes as well as IFN-γ inducing epitopes have a crucial role in humoral and cell-mediated adaptive immune responses by producing antibodies and stimulating macrophages and natural killer cells, prediction of the epitopes currently are highly considered for vaccine design [13]. Subsequently, prediction of discontinuous B-cell epitopes and IFN-γ inducing epitopes were performed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there are some drawbacks associated with conventional vaccines including weak immunity, multi-dose administration, allergenic potential and low safety. Consequently currently, new vaccine platforms such as Subunit Vaccines, DNA vaccine, and multi-epitope vaccine (MEV) are highly regarded [13]. Among them, due to high specificity, safety and low-cost production of MEVs these vaccines have attracted attention.…”
Section: Introductionmentioning
confidence: 99%
“…The main objective of the immunoinformatics is to convert and organize large‐scale immunological data combining statistical and machine learning systems, to obtain immunologically meaningful interpretations (Soria‐Guerra, Nieto‐Gomez, Govea‐Alonso, & Rosales‐Mendoza, ). The proper use of immunoinformatics tools has shown a high degree of accuracy; therefore, this discipline has been employed to characterize molecular interactions between epitopes defining new hypotheses related to understand the immune system mechanisms (Wang et al, ), as well as to develop new multi‐epitope vaccine strategies against emergent viral diseases such as Zika virus (Dikhit et al, ; Pradhan et al, ), and Ebola virus (Dikhit et al, ), or re‐emerging viruses: Hepatitis C virus (Ashraf, Bilal, Mahmood, Hussain, & Mehboob, ) and Dengue virus (Ali et al, ). In this study, we used immunoinformatics approach to characterize both T‐cell and B‐cell epitopes for the main immunogenic protein of CSFV (E2 protein).…”
Section: Methodsmentioning
confidence: 99%